1997
DOI: 10.1007/s002280050320
|View full text |Cite
|
Sign up to set email alerts
|

Use of albumin in two Spanish university hospitals

Abstract: The use of albumin in our centers is incorrect and has important economic repercussions. Some educational and informative measures must be established to change this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 0 publications
1
22
1
4
Order By: Relevance
“…Apenas 8,1% das prescrições foram consideradas apropriadas. Mais de 90,0% dos frascos foram consumidos em prescrições inapropriadas, o que acarretou um impacto de custos importante 13 .…”
Section: Total 16 155unclassified
See 3 more Smart Citations
“…Apenas 8,1% das prescrições foram consideradas apropriadas. Mais de 90,0% dos frascos foram consumidos em prescrições inapropriadas, o que acarretou um impacto de custos importante 13 .…”
Section: Total 16 155unclassified
“…O quando comparados com os obtidos no estudo de Vargas et al 13 , desenvolvido antes da disseminação do protocolo, embora tenham sido realizados com instituições e profissionais diferentes 8 . Um estudo de 1996 num hospital de 850 leitos, na França, comparou os níveis de consumo e os padrões de prescrição, antes e após a difusão de protocolo de albumina humana.…”
Section: Total 16 155unclassified
See 2 more Smart Citations
“…The studies revealed 50 to 70% inappropriate prescriptions, with substantial effects on costs 3,4,7,8,9,10,11 . However, when protocols are in effect, albumin is prescribed more appropriately for the clinical conditions for which it is indicated 4,12 .…”
Section: Introductionmentioning
confidence: 99%